-6y=5+5y-6

Simple and best practice solution for -6y=5+5y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6y=5+5y-6 equation:



-6y=5+5y-6
We move all terms to the left:
-6y-(5+5y-6)=0
We add all the numbers together, and all the variables
-6y-(5y-1)=0
We get rid of parentheses
-6y-5y+1=0
We add all the numbers together, and all the variables
-11y+1=0
We move all terms containing y to the left, all other terms to the right
-11y=-1
y=-1/-11
y=1/11

See similar equations:

| (5x-10)=60 | | (x×x)/2-8=28 | | j/5=-12 | | (X+17)+(4x-5)+63=180 | | 6m+2=-3m-16 | | 8b+9-2=5b+22 | | 20+x=25+x | | 35t+70(7-+)=385 | | (3x-58)=x | | x3-6x-40=0 | | X+17+4x-5+63=180 | | 0.4x+0.4=0.7x-0.5 | | k/5+7=12 | | 5y+35=180-105 | | 0.4+0.4=0.7x-0.5 | | 2x+10=1x-2 | | 42=-5x-8 | | (X+42)=x | | -12+x/3=-20 | | 1/3x+1=-9 | | 3/2h+1=2h+5 | | (2x+10)=x | | (6x)=(4x+16) | | x/4x=3x/12 | | x3+-6x+-40=0 | | 8y+4y-10y=18 | | 3n-1n+7=25 | | R=5x+3(x+15) | | 2(3x-4)+x-1=-+ | | -3r+3(r-2)=-2(r+6) | | 6s+2s+4s-9s+2s=15 | | 3y-3=y+17 |

Equations solver categories